Methods of using the periodic chart in the case of the missing values of the stable AR model (2) - ناصر, جنان عباس (Journal of Economics and Administrative Sciences, 2011)
In this study, we investigate the behavior of the estimated spectral density function of stationary time series in the case of missing values, which are generated by the second order Autoregressive (AR (2)) model, when the error term for the AR(2) model has many of continuous distributions. The Classical and Lomb periodograms used to study the behavior of the estimated spectral density function by using  the simulation.